Determinants of appropriate complementary feeding practices among mothers of children aged 6–23 months in Bokoji town, Oromia region, Ethiopia - Abdurehman Kalu Tololu; Bekele Teshome; Hiwot Zelalem Fessaha; Abdene Weya Kaso (BMC Pediatrics)
Abstract Background One of the contributing factors for malnutrition among children aged 6–23 months is inappropriate complementary feeding. Appropriate complementary feeding practices have the potential to prevent 6% of all deaths among children 6–23 months, particularly in developing countries. Thus, this study aimed to determine the prevalence of appropriate complementary feeding practices and associated factors among mothers aged 6–23 months in Bokoji Town, Oromia Region, Ethiopia. Method A community-based cross-sectional study was carried out among 6–23 aged children in Bokoji town from May 1–30, 2023. A total of 434 mothers of children aged 6–23 months were recruited by simple random sampling technique using computer-generated random numbers. The Collected data were entered into Epi Info version 7 and exported into SPSS version 25 for analysis. Bivariable and multivariable Logistic regression model was used to determine factors associated with appropriate complementary feeding practice. A p-value of < 0.05 and an Adjusted Odds Ratio (AOR) with 95% CI were used to declare the factors associated with the outcome variable. Results The study found that 80.0% (95% CI: 76.0%, 83.5%) of children had a timely introduction of complementary feeding, 19.8% (95% CI: 16.3%, 23.8%) had minimum dietary diversity, 93.8%(95% CI: 91.2%, 95.8%) had minimum meal frequency and 19.4%(95% CI: 15.8%, 23.3%) had minimum acceptable diet. The level of appropriate complementary feeding practice in this study was 13.1%,(95% CI: 10.1%, 16.6%). Husband education level [AOR = 4.32:95% CI:1.68,11.11], Mothers education level [AOR: 3.98, 95% CI:1.64–9.67], birth order [AOR = 13.65:95% CI:3.56, 52.34], Postnatal care visit[AOR: 4.35, 95% CI:1.52,12.49], and place of birth [AOR: 2.97, 95% CI:1.26,6.98] and mothers knowledge of Infant and Youth Child feeding services [AOR: 10.03, 95% CI:2.66, 37.81] were significantly associated with appropriate complementary feeding practice. Conclusion The study found the prevalence of mothers who practiced appropriate complementary feeding is low in the study area. Factors such as the education level of husband and mother, birth order, postnatal care visit, place of birth, and mothers’ knowledge of Infant and Youth Child feeding services were significantly associated with appropriate complementary feeding practice. Thus, healthcare providers should provide continuous health education on complementary feeding during antenatal care visits, postnatal care visits, and child immunization services.